Konrad Adenauer Foundation and Projects Library as the Information and Documentation Center in a Non-government Organization - Örkmez, Cüneyt (Information World, 2001)
Organised knowledge is needed by the non-governmental organizations at the intersity depending upon the seriosity of their work and organizational structure. These organizations, which are indispensible agencies of growing democracies, are alsa effective in the emergence of knowledge-based societies. Konrad Adenauer Foundation, within its wide area of collaboration with the Turkish partners tor the sake of providing studies to support the social, political, economic and cultural development of our country alsa aims at informing the end-user about the foundation’s studies by means publications. The present study resumes the establishment of the Library of Konrad Adenauer Foundation and Projects and its processes of providing user services.